1988
DOI: 10.1901/jaba.1988.21-385
|View full text |Cite
|
Sign up to set email alerts
|

Theft Reduction in a Grocery Store Through Product Identification and Graphing of Losses for Employees

Abstract: Shoplifting and employee theft constitute a major problem for retailers. Previous research has described techniques for effectively reducing either type of theft but has not addressed the problem of thefts of unspecified origin. In a grocery store we evaluated the effect of identifying for employees frequently stolen products from three groups of items and graphing, twice weekly in the lunchroom, losses for the separate groups. After the products were identified and losses graphed, thefts from the three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…In this study, the adaptation of the methodology for use with optical sc~nnlng equipment, as described by Carter et al (1988), was used. Data on all EAN-marked stock entering the store were entered into the computer by two store employees.…”
Section: Measurement Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the adaptation of the methodology for use with optical sc~nnlng equipment, as described by Carter et al (1988), was used. Data on all EAN-marked stock entering the store were entered into the computer by two store employees.…”
Section: Measurement Systemmentioning
confidence: 99%
“…These findings were later replicated (Carter et al, 1979;Carter & Holmberg, 1992;Mart & Mullen, 1993). Carter et al (1988) showed that specific theft data provided as feedback to employees was a cost effective theft reduction method. Cardboard "dllmmf' police have also been shown to reduce retail thefts (Carter et al, 1990).…”
mentioning
confidence: 99%
“…Total sales and thefts of candy products might be relatively constant over time but may increase temporarily for given products as a function of promotional activities. Signs publidy identifying high-risk products (McNees et al, 1976) and other theft prevention measures (Carter et al, 1988) have been demonstrated to reduce thefts for a variety of products without producing a negative effect upon sales. Taken together with the data from this study, the effects of specific product identification (i.e., promotional activities and specific signs to reduce thefts) on sales and thefts appear to be asymmetric.…”
mentioning
confidence: 99%
“…Although behavior analysts have shown that undesirable consumer behavior (i.e., theft) can be reduced with no negative effects upon sales (Carter, Holmstrim, Simpanen, & Melin, 1988;McNees, Egli, Marshall, Schnelle, & Risley, 1976), there seem to be no similar analyses of promotional activities and their effects on sales and theft in retail settings. METHOD: The study was conducted at a grocery store described in previous research (Carter et al, 1988). The store used an optical price scanning system with cash registers connected to a computer that maintained data on sales, prices, and so forth.…”
mentioning
confidence: 99%
See 1 more Smart Citation